4(v-4)-6=-7(-2v+1)-v

Simple and best practice solution for 4(v-4)-6=-7(-2v+1)-v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(v-4)-6=-7(-2v+1)-v equation:


Simplifying
4(v + -4) + -6 = -7(-2v + 1) + -1v

Reorder the terms:
4(-4 + v) + -6 = -7(-2v + 1) + -1v
(-4 * 4 + v * 4) + -6 = -7(-2v + 1) + -1v
(-16 + 4v) + -6 = -7(-2v + 1) + -1v

Reorder the terms:
-16 + -6 + 4v = -7(-2v + 1) + -1v

Combine like terms: -16 + -6 = -22
-22 + 4v = -7(-2v + 1) + -1v

Reorder the terms:
-22 + 4v = -7(1 + -2v) + -1v
-22 + 4v = (1 * -7 + -2v * -7) + -1v
-22 + 4v = (-7 + 14v) + -1v

Combine like terms: 14v + -1v = 13v
-22 + 4v = -7 + 13v

Solving
-22 + 4v = -7 + 13v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-13v' to each side of the equation.
-22 + 4v + -13v = -7 + 13v + -13v

Combine like terms: 4v + -13v = -9v
-22 + -9v = -7 + 13v + -13v

Combine like terms: 13v + -13v = 0
-22 + -9v = -7 + 0
-22 + -9v = -7

Add '22' to each side of the equation.
-22 + 22 + -9v = -7 + 22

Combine like terms: -22 + 22 = 0
0 + -9v = -7 + 22
-9v = -7 + 22

Combine like terms: -7 + 22 = 15
-9v = 15

Divide each side by '-9'.
v = -1.666666667

Simplifying
v = -1.666666667

See similar equations:

| 11x^2+2x+16+(-2x^2)+x+-2= | | 15-(2x+7)= | | -9(5y+3)= | | 12x+10=130 | | u-u+3u-3u+3u=6 | | 7x+6=5x-(3-2x)+9 | | -2(c-5)+3c=4(265-c) | | 7x-20+-10x=11 | | x^2+1.78x^2=3025 | | x+6x^2=16 | | 3.64=x/8 | | 44-2x=9-7x | | 5y-4y=18 | | 8+5*2+3*4=128 | | -5(n-s)= | | 100[0.02(n+6)]= | | 2(x-3)-4x=36 | | 10y-y-5y-6y=8 | | 10-2b=24 | | -60=-15 | | 5(2x-4)-2(x+1)-17x= | | -4(4u-1)+4u=9+3(2u-5) | | (-7x^2y)(-10x^3y^5)= | | 5b-20=15 | | 15q-14q=20 | | (-.75)(-8x)(1.3)(4y)(1)=c | | -3(d-7)+9=27 | | 2x^2+10-600=0 | | 2s+s=15 | | 3.6(x+9)+4.9x= | | -6=z/5-3 | | 14xy-35yz-63xz= |

Equations solver categories